A tapered fibre optics biosensor for histamine detection - Usman, Hamza; Abu Bakar, Muhammad Hafiz; Amir Hamzah, Amir Syahir; Salleh, Abu Bakar (Emerald Group Publishing, 2016)
Purpose: This paper aims to estimate the level of histamine in fish and fish products, as it is very important because of their implication in fish poisoning in humans; hence, ascertaining histamine levels in the aforementioned serves as a chemical index for spoilage. Design/methodology/approach: A technique was developed to immobilize an ordered multilayer of diamine oxidase (DAO) by means of chemical cross-linking on the biconical taper surface stepwisely alternating between chitosan, glutaraldehyde and the enzyme. A spectrophotometric signal results from horseradish peroxidase catalyzed reduction of H2O2, a secondary product of the oxidative deamination of histamine monitored at 450 nm. Findings: The biosensor showed a linear response range up to 1.5 mM, a good sensitivity of 0.64 mM-1 with detection and quantification limits towards histamine of 0.086 mM (15.8 ppm) and 0.204 mM (37.7 ppm) and a linear response range of 0-1.5 mM. It showed a response and recovery time of 14 sec and operational stability up to 40 repeated analyses without significant loss of sensitivity. Practical implications: The developed biosensor has a good potential for use in the quantitative determination of histamine in seafood. Originality/value: The paper described an outcome of an experimental work on tapered fibre optics (taper)-based biosensor coated with DAO embedded into a chitosan membrane to measure histamine.